Bio-energy and rural development: Findings from a comparative study in Central, Eastern and Southern Europe - Axel Wolz; Gertrud Buchenrieder; Richard Márkus (South East European Journal of Economics and Business, 2011)
Rising energy prices for fossil fuels, the unreliable supply of energy imports during recent winters, and European Union (EU) policies have stimulated national awareness and political action on renewable bio-energy among all of the European countries. In discussions on agricultural policy, renewable energy has been advocated as a way to more rural prosperity. In this paper, we assess whether there is any impact on agricultural and rural employment and income as anticipated. Among the new member states (NMS) of the EU, the share of bio-energy is slowly increasing. Yet among the Balkan states and Turkey this process has just started. In both sub-regions an expansion of rape seed cultivation, and to a smaller extent of the production of wood pellets, could be observed. Similarly, the build-up of processing facilities is in its infancy. Up to now, however, its overall impact on agricultural and rural income and employment seems to have been marginal.
Keywords: Q10; Q28; Q42; R11; 330; bio-energy; agricultural development; rural development; Central; Eastern and Southern Europe